Pengaruh Capital Intensity, Inventory Intensity, Komisaris Independen Dan Sales Growth Terhadap Tax Avoidance: (Studi Empiris Pada Perusahaan Sektor Kesehataan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2021) - Anggi Septiani; Eka Rima Prasetya (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
This study aims to test and prove empirically the influence of capital, inventory shortages, commissioner independence and sales growth on tax evasion. The population used in this study are all companies that have been listed on the Indonesia Stock Exchange in the health sector, totaling 12 companies during the 5 year observation period (2017-2021), where the number of samples to be used will use a purposive sampling technique. The analytical tool for testing the hypothesis or the type of research used in this study is EViews version 10. The data analysis method uses descriptive statistical analysis, classic assumption test and hypothesis testing. The results of this study indicate that capital intensity, inventory intensity, independent commissioners and sales growth simultaneously have a positive and significant effect on tax avoidance, and partially research capital intensity, sales growth have a positive and significant effect on tax avoidance and the results of research on inventory intensity and independent commissioners no effect on tax avoidance.